2020
DOI: 10.1186/s12883-020-01888-w
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of age group classification for risk stratification in glioma patients

Abstract: Background: Age is associated with the prognosis of glioma patients, but there is no uniform standard of agegroup classification to evaluate the prognosis of glioma patients. In this study, we aimed to establish an age group classification for risk stratification in glioma patients. Methods: 1502 patients diagnosed with gliomas at Nanfang Hospital between 2000 and 2018 were enrolled. The WHO grade of glioma was used as a dependent variable to evaluate the effect of age on risk stratification. The evaluation mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 48 publications
4
49
0
Order By: Relevance
“…WHO grade 1 and 2 gliomas are considered low- grade gliomas (LGG), while grades 3 and 4 are classified as high-grade gliomas (HGG). Glioblastoma multiforme (GBM, WHO grade 4) is the most aggressive type of glioma with poor prognosis and median survival of about 15 months, even after multimodal therapy [2]. However, this classification has been modified in the most recent WHO classification.…”
Section: Introductionmentioning
confidence: 99%
“…WHO grade 1 and 2 gliomas are considered low- grade gliomas (LGG), while grades 3 and 4 are classified as high-grade gliomas (HGG). Glioblastoma multiforme (GBM, WHO grade 4) is the most aggressive type of glioma with poor prognosis and median survival of about 15 months, even after multimodal therapy [2]. However, this classification has been modified in the most recent WHO classification.…”
Section: Introductionmentioning
confidence: 99%
“…Formyl peptide receptor 2 (FPR2) is classified as the formyl peptide receptor (FPR) family subordinated to the GPCR superfamily. FPR2 as well as FPR1 participate in multiple intracellular signaling pathways ranging from activation of various protein kinases and phosphatase to tyrosine kinase receptors transactivation [16, 17, 21, 23]. The significance of these crucial cellular pathways within cells also suggested that any dysfunction of the activated pathways could lead to disorder within the body [47].…”
Section: Discussionmentioning
confidence: 99%
“…Of all adult primary brain tumours, glioblastoma (median age of 46.3 years at diagnosis [ 3 ]) is the most common (56.6%) and most aggressive for which there is no curative treatment [ 4 ]. Recent evidence suggests that there has been a significant increase in the incidence of glioblastoma from 1995 to 2015 more than doubling from 2.4 to 5.0 per 100,000 in the UK, whereas the rest of gliomas remained stable [ 5 ].…”
Section: Epidemiology and Classification Of Adult Gliomasmentioning
confidence: 99%
“…Glioblastoma may develop rapidly without evidence of a less malignant precursor lesion (primary glioblastoma or ‘de novo’ glioblastoma), or through progression from a lower grade tumour (secondary glioblastoma). Low grade gliomas (astrocytoma, and oligodendrogliomas grade II) normally affect young adults (median age at diagnosis is 35 years for grade II astrocytoma and 34.8 years for grade II oligodendrogliomas [ 3 ]) with a survival average of approximately 7 years for patients affected by astrocytomas and more than 15 years for those who have developed oligodendrogliomas [ 9 ]. Although low grade glioma patients have better survival rates compared to patients with high grade glioma, all low grade gliomas are invasive and eventually progress to high grade glioma (grade III/IV) leading to death [ 9 ].…”
Section: Epidemiology and Classification Of Adult Gliomasmentioning
confidence: 99%